(untitled) (Journal of Social Sciences Review, 2023)
The current study aimed to investigate differences between medical and engineering students on suicidal ideation, anxiety, depression and life satisfaction and also investigated the relationship among these variables. A purposive sample of 200 students, including 100 medical students (50 male and 50 female) and 100 engineering students (50 male and 50 female), age 19 through 27 was drawn from students of medical and engineering colleges of Lahore. Satisfaction with Life Scale,GAQ-7 for anxiety, PHQ-7 for depression and SBQ-R for Suicidal Ideation were used to collect data from the participants.The results of t-test indicated that there was significant difference between medical and engineering students in terms of suicidal ideation and life satisfaction. The results of stepwise regression analysis indicated that depression and anxiety were significantly positive predictors of suicidal ideation, whereas life satisfaction was a significant negative predictor of suicidal ideation. The findings of this study can contribute in understanding suicidal ideation in medical and engineering students of Pakistan and is likely to contribute in further research on the topic.